Phagocyte Transcriptomic Analysis Reveals Focal Adhesion Kinase (FAK) and Heparan Sulfate Proteoglycans (HSPGs) as Major Regulators in Anti-bacterial Defense of Crassostrea hongkongensis - Lin, Yue; Mao, Fan; Wong, Nai-Kei; Zhang, Xiangyu; Liu, Kunna; Huang, Minwei; Ma, Haitao; Xiang, Zhiming; Li, Jun; Xiao, Shu; Zhang, Yang; Yu, Ziniu (Frontiers in Immunology, 2020)
Invertebrates generally lack adaptive immunity and compensate this with highly efficient innate immune machineries such as phagocytosis by hemocytes to eradicate invading pathogens. However, how extrinsically cued hemocytes marshal internal signals to accomplish phagocytosis is not yet fully understood. To this end, we established a facile magnetic cell sorting method to enrich professional phagocytes from hemocytes of the Hong Kong oyster (Crassostrea hongkongensis), an ecologically and commercially valuable marine invertebrate. Transcriptomic analysis on pre-sorted cells shows that phagocytes maintain a remarkable array of differentially expressed genes (DEGs) that distinguish them from non-phagocytes, including 352 significantly upregulated genes and 479 downregulated genes. Pathway annotations reveal that focal adhesion and ECM-receptor interactions were the most conspicuously enriched pathways in phagocytes. Phagocytosis rate dramatically declined in the presence of an FAK inhibitor, confirming importance of the focal adhesion pathway in regulating phagocytosis. In addition, we also found that heparan sulfate proteoglycans (HSPGs) families were lineage-specifically expanded in C. hongkongensis and abundantly expressed in phagocytes. Efficiency of phagocytosis and hemocytes aggregation was markedly reduced upon blockage of endogenous synthesis of HSPGs, thus implicating these proteins as key surface receptors in pathogen recognition and initiation of phagocytosis.